2023
DOI: 10.1186/s12936-023-04467-9
|View full text |Cite
|
Sign up to set email alerts
|

An insight to better understanding cross border malaria in Saudi Arabia

Abstract: Background Border malaria is a major obstacle for the malaria elimination in Saudi Arabia. Today, the southern border of Saudi Arabia is a region where malaria cases are resurging, and malaria control is dwindling mainly due to the humanitarian crisis and the conflict in Yemen. This study analyses the current border malaria epidemiology along the southern border of Saudi Arabia from 2015 to 2018. Methods All reported cases maintained by the malaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 72 publications
2
12
0
Order By: Relevance
“…The results of the study indicate that Plasmodium falciparum is the dominant malaria parasite in Jazan which is similar to the finding of the study that found that (94.3%) were infected with Plasmodium falciparum [8]. This research emphasises the need for focused treatments to control and prevent Plasmodium Plasmodium falciparum in Jazan, which has yet to reach elimination but has achieved public health achievements [19]. In contrast, the central provinces of KSA (Riyadh, Qassim, and Ta'if) showed varying percentages of malaria species infections, with the dominance of Plasmodium vivax and Plasmodium ovale over the five years of the study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of the study indicate that Plasmodium falciparum is the dominant malaria parasite in Jazan which is similar to the finding of the study that found that (94.3%) were infected with Plasmodium falciparum [8]. This research emphasises the need for focused treatments to control and prevent Plasmodium Plasmodium falciparum in Jazan, which has yet to reach elimination but has achieved public health achievements [19]. In contrast, the central provinces of KSA (Riyadh, Qassim, and Ta'if) showed varying percentages of malaria species infections, with the dominance of Plasmodium vivax and Plasmodium ovale over the five years of the study.…”
Section: Discussionsupporting
confidence: 85%
“…The findings showed that the percentage of malaria cases in the KSA in 2021 that were either locally introduced or imported. The results reveal that no local cases were reported, and only Jazan and Aseer had introduced cases, whereas all other provinces had imported cases [19,16]. This illustrates the continuous problem of imported malaria in the KSA, notably among migrant workers from East Africa, Yemen and South Asia.…”
Section: Discussionmentioning
confidence: 97%
“…In Saudi Arabia, imported malaria remains a major problem with a constant flow of imported malaria, mostly among immigrant workers from south Asia (Pakistan, India and Bangladesh), East Africa (Sudan and Ethiopia), and Yemen. [6][7][8] In the current study, a total of 493 suspected patients were tested; CBFME identified 34 (6.89%) while CareStart RDT kit identified 29 (5.88%). Moreover, Using CBFME as reference, CareStart RDT kit failed to detect 5 positive cases that were confirmed by microscopy as P vivax (3) and P falciparum (2).…”
Section: Hassanein Et Al • Medicine (2023) Medicinementioning
confidence: 79%
“…Additionally, Plasmodium parasites can also be transmitted either from a mother to her baby during pregnancy (trans-placentally) or through contaminated blood transfusion from an infected blood donor. [4,5] The Global incidence of malaria is increasing due to 3 main factors that play an important role in disease transmission; factors due to human immunity, migrations to malaria epidemic areas and imported malaria cases into non-endemic countries, [6][7][8] factors related to the vector increasing breeding possibilities that result from climatic and ecological conditions, such as rainfall patterns, humidity, water reservoirs, presence of plants, change in whether patterns, appearance of new vectors by the continuous broken down of vectors control programs due to lack of quality control and growing insecticide resistance. [5,9] Finally, factors directly related to the parasite, as the appearance of resistance to conventional anti-malarial drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation